Home Biofeedback Versus Physical Therapy for Stress Urinary Incontinence: A Randomized Trial. Issue 10 (16th October 2021) - Barnes, Kara Lauren; Cichowski, Sara; Komesu, Yuko M.; Jeppson, Peter C.; McGuire, Brenna; Ninivaggio, Cara S.; Dunivan, Gena C.
Abstract : Objective: The aim of the study was to assess whether home biofeedback is noninferior to supervised pelvic floor physical therapy (PFPT) for the treatment of stress urinary incontinence (SUI) in women. Methods: The study used a randomized controlled noninferiority trial to compare a home biofeedback device with PFPT. Women older than 18 years with SUI and no history of a prior incontinence surgery or PFPT were eligible. Forty-two participants were required to determine noninferiority for the primary outcome, improvement in quality of life as measured by the International Consultation on Incontinence Questionnaire Short Form. The noninferiority margin was 4 points. Secondary outcomes included sexual function, overactive bladder symptoms, and patient impression of improvement. Results: From June 2018 to October 2019, 54 women with SUI were recruited (27 biofeedback, 27 PFPT) and 43 (21 biofeedback, 22 PFPT) completed follow-up. The groups had comparable baseline characteristics. For the primary outcome of change in mean International Consultation on Incontinence Questionnaire–Short Form scores (where lower scores indicate less incontinence), home biofeedback was found to be noninferior to PFPT with a mean decrease from baseline of −3.95 (95% confidence interval [CI] = −2.21 to −5.70) in the home biofeedback group versus −4.73 (95% CI = −3.21 to −6.25) and −3.95 (95% CI = −2.21 to −5.70) in the PFPT group ( P = 0.009). The PFPT group showed more improvement in overactive bladder symptoms, but not in incontinence severity without difference in sexual function. Conclusions: Home biofeedback was noninferior to PFPT for the primary treatment of SUI in women at 3 months. These results support the use of personal biofeedback devices for the treatment of SUI. Clinical Trial Registration: ClinicalTrials.gov, http://www.clinicaltrials.gov, NCT03443687.